The Challenge of ICIs Resistance in Solid Tumours: Could Microbiota and Its Diversity Be Our Secret Weapon? - Roberto, Michela; Carconi, Catia; Cerreti, Micaela; Schipilliti, Francesca Matilde; Botticelli, Andrea; Mazzuca, Federica; Marchetti, Paolo (Frontiers in Immunology, 2021)
The human microbiota and its functional interaction with the human body were recently returned to the spotlight of the scientific community. In light of the extensive implementation of newer and increasingly precise genome sequencing technologies, bioinformatics, and culturomic, we now have an extraordinary ability to study the microorganisms that live within the human body. Most of the recent studies only focused on the interaction between the intestinal microbiota and one other factor. Considering the complexity of gut microbiota and its role in the pathogenesis of numerous cancers, our aim was to investigate how microbiota is affected by intestinal microenvironment and how microenvironment alterations may influence the response to immune checkpoint inhibitors (ICIs). In this context, we show how diet is emerging as a fundamental determinant of microbiota’s community structure and function. Particularly, we describe the role of certain dietary factors, as well as the use of probiotics, prebiotics, postbiotics, and antibiotics in modifying the human microbiota. The modulation of gut microbiota may be a secret weapon to potentiate the efficacy of immunotherapies. In addition, this review sheds new light on the possibility of administering fecal microbiota transplantation to modulate the gut microbiota in cancer treatment. These concepts and how these findings can be translated into the therapeutic response to cancer immunotherapies will be presented.